Electric Symmetric Dipole Modes Enabling Retroreflection from an Array Consisting of Homogeneous Isotropic Linear Dielectric Rods. Issue 17 (25th May 2020) - Cao, Xiyuan; Wang, Qianjing; Wan, Pengcheng; Zhang, Weiping; Lin, Zhifang; Chui, Siu Tat; Du, Junjie
Abstract: Linear‐dielectric‐based in‐plane optical design is attractive yet challenging in nano‐optical technologies when combined with the compatibility with complementary metal‐oxide‐semiconductor technology. Here, by exciting an electric symmetric dipole mode (ESDM), exploiting the interplay between an electric quadrupole mode and a magnetic dipole mode in a homogeneous isotropic linear dielectric rod, an in‐plane retroreflector is successfully realized in the case of no dependence on asymmetry arising from anisotropic/bianisotropic materials, complex unit cell, or asymmetric environments. The ESDM is analogous to an electric dipole (ED) in the sense that its radiation is overwhelmingly dominant in the forward and backward directions, while its phase symmetry is in stark contrast to the antisymmetry of ED modes. The studies herein show symmetric dipole modes are one of general mechanisms for retroreflection. Such a retroreflector combines many other outstanding advantages such as low loss, unitary efficiency, and simple configuration with low fabrication demands. The in‐plane manipulation for waves makes it an appealing platform for manipulating particles and developing on‐chip optical cavities, light sources in integrated optical circuits, optical parametric oscillators, and interferometers. Abstract : An electric symmetric dipole mode, analogous to an electric dipole in the sense that its radiation is overwhelmingly dominant in the forward and backward directions, but in stark contrast to the latter in symmetry nature of its phase distributions, can be excited. It supports an array consisting of homogeneous isotropic linear dielectric rods in air to produce retroreflection behavior.